The Urgency of Reforming Law Enforcement Institutions in Handling Children Who Commit Crimes in Indonesia - Abdul Bari; Achmad Taufik (International Journal of Social Welfare and Family Law, 2025)
This study examines the urgency of reforming law enforcement institutions in handling child offenders in Indonesia. The enactment of Law No. 11 of 2012 on the Criminal Justice System for Children (SPPA) marked a paradigm shift from retributive justice to restorative justice. However, its implementation has not been optimal because law enforcement institutions are still sectoral and not integrated. This study uses a normative juridical approach with empirical juridical support to analyse the conformity of legal norms with institutional practices. Data were obtained from legislation, scientific literature, and interviews with law enforcement officials and child protection practitioners. The results show that the implementation of diversion is still low due to weak coordination between institutions, limited human resources, and the absence of an integrated institutional mechanism. Institutional reform is needed to strengthen synergy between institutions, foster a humanistic mindset among officials, and ensure child protection in accordance with the principles of restorative justice. This study recommends the establishment of a permanent coordination body between child law enforcement agencies and ongoing training for officials. Institutional reform is seen as a strategic step towards realising a juvenile justice system that is not only normative but also substantively fair and restorative.